Anti-collapse performance of composite frame with special-shaped MCFST columns. (15th October 2021) - Gao, Shan; Guo, Lanhui; Zhang, Zhao
Highlights: A composite frame with special-shaped MCFST columns was tested in the scenario of middle-column loss. The fracture of the bottom beam flange caused the failure of the frame eventually. The designed frame exerts good robustness to resist progressive collapse. The length of side plate exhibits more influence on the performance of the frame than the thickness of side plate. Abstract: A spatial steel frame with concrete slab and special-shaped multi-partition concrete filled steel tubular columns was tested in a simulated scenario of progressive collapse. The load-deformation relationship of the frame with damaged middle column under vertical load is discussed. Parametric analysis is also conducted by using a validated FE model. The results show that the failure of the specimen resulted from the fracture of the bottom beam flange eventually. The configuration of side plate connection and multi-partition concrete filled steel tubular column both could provide a reliable load-redistribution path for additional loads due to single column loss. The designed frame exerts good robustness to resist the collapse resulting from middle column loss. The simulation shows that single-column removal would cause additional lateral force and moment on the adjacent columns, besides axial force. The length of side plate exhibits more influence on the performance of the frame than the thickness of side plate.